Characterization of the running-in period in total hip resurfacing arthroplasty: an in vivo and in vitro metal ion analysis - Heisel, Jens Christian; Streich, Nikolaus; Krachler, Michael; Jakubowitz, Eike; Kretzer, Jan Philippe (The journal of bone & joint surgery. A, American volume, 2008)
Background: Metal-on-metal total hip resurfacing arthroplasty is increasingly being performed in young and active patients. Preclinical in vitro testing of implants is usually performed with use of hip simulators, and the serum metal ion concentration is determined for the purpose of monitoring the patients. The goal of this study was to characterize the early running-in period in vivo and in vitro by characterizing metal ion levels. - Methods: A well-functioning total hip resurfacing prosthesis was implanted in fifteen consecutive patients, and the serum metal ion concentrations in these patients were then determined preoperatively and at intervals during the first postoperative year (at one, six, twelve, twenty-four, and fifty-two weeks). The number of walking cycles was measured with use of a computerized accelerometer in order to compare walking cycles to hip simulator cycles. In vitro, five similar components were investigated for 3 million cycles with use of a hip simulator. Serum samples were obtained at different time points, and wear was measured by quantifying wear particles and ions in the samples. All patient and simulation serum samples were analyzed with use of inductively coupled plasma-mass spectrometry. One simulator implant was investigated with use of scanning electron microscopy. - Results: The serum chromium and cobalt levels of the patients continuously increased during the first six months and showed an insignificant decrease thereafter. The molybdenum concentration was unchanged compared with preoperative values. In contrast, the simulator measurements showed a different wear pattern with a high-wear running-in period and a low-wear steady-state phase. The running-in period was delayed by 300,000 cycles and lasted up to 1 million cycles. Scanning electron microscopic analysis showed a carbon-rich protein film predominantly in the early phases of simulation. Scratches were detected originating from pits filled with aluminum oxide and silicon oxide and from pulled-out carbides that were causing third-body wear. - Conclusions: The simulator study allowed an exact characterization of the running-in period and showed a delayed onset of running-in wear. In contrast, the clinical data showed a slow increase in measured ion concentrations. These different wear patterns are probably due to the effects of distribution, accumulation, and excretion of particles and ions in vivo. - Level of Evidence: Therapeutic Level IV. See Instructions to Authors for a complete description of levels of evidence.